How does environmental regulation promote green technology innovation in enterprises? A policy simulation approach with an evolutionary game - Zhang, Zhenhua; Shi, Ke; Gao, Yue; Feng, Yanchao (Journal of environmental planning and management, 2025)
To vividly illustrate the dynamic interactions between government and enterprise in China, a non-cooperative evolutionary game is employed. Simulations are conducted to examine the effectiveness of environmental regulations in promoting green technology involving multiple policy instruments for yielding the ideal outcome. In particular, numerical simulations are introduced to explore the asymptotic stability of various evolutionary stabilization strategies. It is shown that appropriate coordination of these policy instruments can improve policy effectiveness. The effect of increasing environmental tax collection combined with the gradual innovation special subsidy policies is more effective than separate policies. Moreover, under the necessary supervision intensity, the ideal evolutionarily stable equilibrium of incentive environmental regulation tools to promote enterprise green technology innovation is easier to achieve. Furthermore, three extended scenarios using the Porter hypothesis are investigated regarding enterprise innovation performance, intellectual property protection, and income tax collection.